Effective lifecycle management of healthcare applications : achieving best practices by using a portfolio framework - Houston, Susan M. (Susan Murphy); Kennedy, Ryan D. (Boca Raton : CRC Press, Taylor & Francis, 2020)
"The rapid growth of software applications within healthcare organizations has made it essential to have defined methodologies and formal processes for the management of the entire IT portfolio. Utilizing a portfolio management framework throughout an application's lifecycle will provide the necessary structure to ensure that all new applications are properly evaluated, and once implemented, remain relevant while continuing to meet organizational requirements. While an organization may have a few large 'organization-wide' systems such as the EHR, lab or radiology systems, they also have a large quantity of other clinical, administrative and research systems. Some larger organizations now have hundreds of software applications to support and manage. The Information Technology (IT) staff must be able to implement new requests while still maintaining the current application portfolio. Utilizing a standard, repeatable, process will help to manage these large portfolios of software applications. This book will review the management of applications throughout their lifecycle, from initial request through disposition. Best practices dictate that every newly requested application undergoes analysis followed by an approval decision from the organization's governance committee. The initial implementation project must include activities to prepare for ongoing support while ensuring the application is compliant with all security, privacy and architecture requirements. An application spends years in operations and maintenance where changes occur regularly through configuration and release management, or additional projects. The cycle continues until disposition. Understanding when to dispose of an application is just as important as deciding when to implement a new one. A defined process for disposing of an application ensures all parts are properly removed or destroyed"--Provided by publisher.
Project Management Overview -- New Application Request Management -- Governance -- Initial Implementation Project -- Transition to Support -- Operations and Maintenance -- Application Disposition
OCLC-licensed vendor bibliographic record.
Keywords: Medical informatics; MEDICAL / Hospital Administration & Care; BUSINESS & ECONOMICS / Project Management; BUSINESS & ECONOMICS / Information Management